2017
DOI: 10.1038/s41598-017-11997-1
|View full text |Cite
|
Sign up to set email alerts
|

The hUC-MSCs cell line CCRC-1 represents a novel, safe and high-yielding HDCs for the production of human viral vaccines

Abstract: MRC-5 represents the most frequent human diploid cells (HDCs)-type cell substrate in the production of human viral vaccines. However, early-passage MRC-5 is diminishing and, due to both technical and ethical issues, it is extremely difficult to derive novel HDCs from fetal lung tissues, which are the common sources of HDCs. Our previous studies suggested that human umbilical cord may represent an alternative but convenient source of new HDCs. Here, we established a three-tiered cell banking system of a hUC-MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Numerous studies have shown that hUC-MSCs have significant immune modulation and tissue repair functions due to their low immunogenicity [14][15][16]. As an ideal candidate for allogenic adoptive transfer therapy, hUC-MSCs have been shown to play a protective role in A/H5N1-associated acute lung injury [17].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that hUC-MSCs have significant immune modulation and tissue repair functions due to their low immunogenicity [14][15][16]. As an ideal candidate for allogenic adoptive transfer therapy, hUC-MSCs have been shown to play a protective role in A/H5N1-associated acute lung injury [17].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown hUC-MSCs play significant immune-modulation and tissue repair functions for its low immunogenicity [13][14][15]. As an ideal candidate for allogenic adoptive transfer therapy, hUC-MSCs have been shown to play a protect role in A/H5N1-associated acute lung injury [16], Although one article have been published recently on the therapeutic effects of stem cells on COVID-19, it is about bone marrow mesenchymal stem cells [17],and did not focus on the treatment of severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In general, HUC-MSC treatment of viral diseases improves clinical symptoms by regulating the immune function of the patients. Importantly, HUC-MSCs are a safe and feasible source of human diploid cells (HDCs) for the production of antiviral vaccines [ 89 ].…”
Section: Main Textmentioning
confidence: 99%